PENGARUH PENERAPAN TEKNIK BISNIS BERESIKO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PANCUNG SOAL - Marlina, Yeni; Rahmi, Rahmi; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
The background from this research is a low comprehension studentsâ mathematics concept at SMPN 1 Pancung Soal. The aim from this research is to know the comprehension studentsâ mathematics which use Bisnis Beresiko Technique more better from a comprehension studentsâ with use a conventional learning. A kind from this research is experiment with random design to subject. The instrument is study kuesioner effectiviness and comprehension studentsâ mathematics test like essay with reliability test is Â = 0,85. Analysis data technique which use is t-test in one side with Minitab. According to the hypothesis, the result P-value = 0,023 more smaller from Î± = 0,05, so that the hypothesis research is accepted. The conclusion from this research is a comprehension studentsâ mathematics with use Bisnis Beresiko Technique more better from with use conventional learning.